Donor–acceptor conjugated ladder polymer via aromatization-driven thermodynamic annulation. Issue 13 (31st January 2018) - Lee, Jongbok; Kalin, Alexander J.; Wang, Chenxu; Early, Julia T.; Al-Hashimi, Mohammed; Fang, Lei
Abstract : The construction of coplanar conjugated ladder polymers featuring alternating donor–acceptor units has been achieved in high efficiency using ring-closing olefin metathesis. Abstract : Composed of alternating electron-rich and electron-deficient repeating units in a fused rigid backbone, donor–acceptor conjugated ladder polymers represent a class of promising material candidates possessing a host of intriguing properties. These polymers are challenging to synthesize because of the typically low reaction efficiency of electron-deficient acceptor units and the possibility of defect formation during the postpolymerization annulation. Herein we report the synthesis of a well-defined donor–acceptor ladder polymer, which overcame these challenges by utilizing aromatization-driven thermodynamic ring-closing olefin metathesis. The good solubility of the polymer allowed for the comprehensive investigation of its optical properties, intramolecular charge transfer, complex formation with dopant, and thin film processing. These results provide a foundation for future applications of donor–acceptor ladder polymers in electronic and optoelectronic devices.